StresSeed: The Unfolded Protein Response During Seed Development - Vitale, Alessandro; Pedrazzini, Emanuela (Frontiers in Plant Science, 2022)
During seed development, the endoplasmic reticulum (ER) takes care of the synthesis and structural maturation of very high amounts of storage proteins in a relatively short time. The ER must thus adjust its extension and machinery to optimize this process. The major signaling mechanism to maintain ER homeostasis is the unfolded protein response (UPR). Both storage proteins that assemble into ER-connected protein bodies and those that are delivered to protein storage vacuoles stimulate the UPR, but its extent and features are specific for the different storage protein classes and even for individual members of each class. Furthermore, evidence exists for anticipatory UPR directly connected to the development of storage seed cells and for selective degradation of certain storage proteins soon after their synthesis, whose signaling details are however still largely unknown. All these events are discussed, also in the light of known features of mammalian UPR.